Digital Transformation Strategy: Behavioral Change Approach in Increasing Technology Adaptation in the Corporate Environment: Case Study of PT Hutama Karya (Persero) - Audy Aditriananda; Achmad Ghazali (Eduvest - Journal of Universal Studies, 2025)
The rapid advancement of digital technologies has driven state-owned enterprises (SOEs) in Indonesia to adopt transformasi digital strategies. PT Hutama Karya (Persero), despite investing billions of Rupiah annually in digital initiatives, continues to face delays and underutilization of tools such as BIM, PMIS, and CDE. This study investigates the root causes of these inefficiencies, arguing that misalignment between strategi digital and behavioral adoption at the project level is the core issue. Using a qualitative case study approach, data were collected from internal documents, interviews, questionnaires, and group discussions. Analysis revealed that resistance to change, lack of practical training, and weak cultural reinforcement are key inhibitors. The study integrates Kotter’s 8-Step Model, ADKAR, and the Theory of Planned Behavior to develop a behavioral-driven transformation framework. Findings highlight high employee motivation but moderate support in process and technology readiness. Business solutions include digital champions, targeted training, broader tool access, and performance-based reinforcement. A phased roadmap (Transform–Sustain–Strive) aligned with RJPP 2025–2029 was proposed, along with a risk mitigation plan. This research contributes to transformasi digital literature by emphasizing behavioral change and offering a replicable framework for SOEs in construction and infrastructure sectors.